Peaks, Spikes, and Barrels : Modeling Sharp Movements in Oil Prices - Pant, Malika (IMF Working Papers; Working Paper ;, 2010)
Global oil markets were roiled by sharp price swings in 2008, and economists are still divided over the reasons for the unusual volatility. Those emphasizing fundamentals point to inelastic supply and demand curves, others view the phenomenon mostly as a result of financial investors flocking into commodity markets. This paper attempts to infer the strength of these competing hypotheses, using a simultaneous equation model that enables us to undertake a separate analysis of supply and demand factors. The model broadly captures both the surge and subsequent fall in prices, with a particularly strong impact of demand factors. The model captures a strong effect of a measure for global liquidity but does not find support for a speculative motive.